Digital Communication Technologies in Public Administration: A Study of Ministry of Basic and Secondary Education, Delta State - Urhibo, Bridget Onajite; Aruoren, Emmanuel Ejiroghene; Ivwighren, Hannah Emoubosa; Imene, Ogheneruemu Rose (Journal of Ecohumanism, 2024)
This study investigates the role of digital communication technologies in enhancing public administration using Ministry of Basic and Secondary Education as a case study. The objectives were on exploring the impact, finding out the opportunities and identifying the challenges of digital communication technologies. Through a comprehensive analysis of survey data from 146 respondents, the study explores various dimensions of digital communication technologies’ influence on citizen engagement, consumer behaviour, and public service delivery. The findings reveal positive perceptions of digital technologies among respondents, highlighting their potential to improve citizen engagement, streamline public service delivery, and overcome traditional barriers to communication. Despite challenges such as limited infrastructure and connectivity issues and infringe of privacy, respondents recognize the transformative impact of digital technologies on public administration processes. Based on the findings, two key recommendations emerge: first, governments should prioritize investment in digital infrastructure to expand internet access and enhance digital literacy among citizens. Second, capacity building and training programs should be implemented to equip public administrators with the skills needed to effectively leverage digital tools for service delivery and citizen engagement. This study underscores the importance of embracing digital communication technologies in public administration and provides valuable insights for policymakers, administrators, and practitioners seeking to harness the full potential of digitalization in governance.